KORREKT OPTRÆDEN: Performative aspekter af politi og politiarbejde - Kvist, Camilla; Holmberg, Lars (Tidsskriftet Antropologi, 2000)
Critical researchers in contemporary police studies argue that the celebrated role of the police as “crime fighters” is but an illusion. But such criticism disregards the symbolic dimensions of police work. This article presents an analysis of different kinds of police performances and shows how officers use performative strategies, both in order to meet the public‘s expectations of them, and in order to make their own working conditions controllable, predictable, and in tune with their idea of what constitutes “real police work”. Even though this concept may be said to be more of an illusion than a reality, it provides the framework for most police work. Police officers and citizens share the belief that the police can and do in fact fight crime, and this shared belief makes it possible for the police to maintain what could be termed their performative efficiency.